Phonopragmatic and Perlocutionary Effects in Islamic Motivational Rhetoric: A Case Study of Mufti Menk's Preaching - Saadiah, Nur Khofifah; Syafii, Muhammad Hisyam; Ibragimov, Sardorbek (Journal of Islamic Communication and Counseling, 2025)
This study fills in the important void in phonopragmatic analyzes of Islamic motivating rhetoric in digital environments, especially how prosodic elements define doctrinal meaning and perlocutionary effects. This study seeks to understand how strategic suprasegmental phonological elements are used to produce convincing religious communications across cultural borders. Methodologically, this study uses a qualitative phonopragmatic approach, combining phonetic analysis with pragmatic interpretation. It uses PRAAT Software in Mufti Menk's lecture "Allah Has A Beautiful Plan for You!" Through systematic segmentation, phonetic transcription, and analysis of prosodic-pragmatic correlations, the study shows that specific intonation patterns associate with particular speech acts and intentions—level tones mark prayer-like closings, while high-rise intonations signal expressive or interrogative utterances. This study establishes the study of spiritual rhetoric by integrating phonological and pragmatic dimensions, offering both academic insights and practical contributions to more effective digital preaching strategies in modern Islamic communication.